Utilizing cylindrical and cubical specimens with edge notch to determine size-independent fracture quantities of rock materials (Fracture and Structural Integrity, 2025)
The compliance method was first applied to short rod specimens to determine the nonlinear fracture toughness of rock materials by ISRM (International Society for Rock Mechanics) in the 1980s. In this study, utilizing the techniques of the J-integral and the crack closure integral (CCI), crucial linear elastic fracture mechanics expressions for straight-notched disk bending (SNDB) specimens, whose tests are simpler than those for short bar specimens, and single-notch cube bending (SNCB) specimens are initially derived to estimate crack propagation states in rock samples. Andesite-based SNDB specimens from the literature are examined using the compliance approach, and a strong correlation is observed between the compliance approach and the nonlinear approach reported in the literature. Subsequently, limestone-based SNCB specimens and beams containing cracks are produced and tested under bending. The fracture test data are estimated using the peak load approach, and the results of the comparative analysis are found to be satisfactorily consistent for both beams and SNCB specimens. The findings of this study reveal that the non-Hookean fracture quantities of rocks can be adequately determined using SNDB and SNCB specimens of a single size.
Keywords: Crack Closure Integral (CCI); Double-K model; Single notched cube bend specimen; Straight-notched disk bend specimen; Two-parameter model (TPM)